2022
DOI: 10.3390/su141912693
|View full text |Cite
|
Sign up to set email alerts
|

Would You Accept Virtual Tourism? The Impact of COVID-19 Risk Perception on Technology Acceptance from a Comparative Perspective

Abstract: Due to the COVID-19 pandemic, the tourism industry and its stakeholders have tried to develop a new virtual tourism market, but its effectiveness remains to be tested. We proposed and tested a new measurement scale composed of ease of use, usefulness, autonomy, enjoyment, perceived risk of COVID-19, and attitude. In total, 274 questionnaires were collected by the purposive sampling method and 239 of them were valid, with 57 potential virtual tourists (who knew of but had not used VR in tourism) and 182 actual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…El-Said and Aziz (2021) and Li et al . (2022a, b) implied that RP from the COVID-19 pandemic leads tourists to consider VR tourism as an alternative. Therefore, it suggested that the higher the TRP during the Zero COVID-19 policy period, the greater the change in PV and the greater the preference for UVTT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…El-Said and Aziz (2021) and Li et al . (2022a, b) implied that RP from the COVID-19 pandemic leads tourists to consider VR tourism as an alternative. Therefore, it suggested that the higher the TRP during the Zero COVID-19 policy period, the greater the change in PV and the greater the preference for UVTT.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulus-organism-response (SOR) model has been widely used in current research in order to explore and understand the process of change in individual behavior (Mehrabian and Russell, 1974). Furthermore, studies exploring TIs based on SOR are often considered (Li et al ., 2022a, b). However, Wu and Lai (2022) have recommended exploring other emotional and psychological factors within the SOR model, even though they have detected the presence of factors such as emotional involvement, flow state and enjoyment.…”
Section: Introductionmentioning
confidence: 99%
“…Even though VR can help tourism recover, the tourism industry needs to explore practical ways to attract potential tourists before any significant financial investments. The problem is that tourists may not want to pay for it and may not accept virtual technology and adapt to virtual tourism (Li et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors also consider it necessary to understand how VR can assist the brand sustainability of tourist destinations after the availability of on-site tourism. Simplifying the use of VR applications will increase the effectiveness of virtual tourism in the future (Li et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%